Evaluation of purified UspA from Moraxella catarrhalis as a vaccine in a murine model after active immunization. - Chen, D (1996)
Moraxella catarrhalis causes otitis media, laryngitis, and respiratory infections in humans. A high-molecular-weight outer membrane protein from this bacterium named ubiquitous surface protein A (UspA) is present on all isolates. A monoclonal antibody (MAb) to UspA that recognizes a conserved epitope of this protein has been shown to promote pulmonary clearance of bacteria in passively immunized mice. In the present study, M. catarrhalis heterologous isolates were screened by dot blot with a panel of four additional MAbs specific for surface-exposed epitopes of UspA from M. catarrhalis isolate 035E. Three of the MAbs were specific for 035E, and the fourth reacted with 17 (74%) of the 23 isolates tested. Thus, UspA contains highly conserved, semiconserved, and variable surface-exposed epitopes. The UspA was purified from the 035E isolate by ion-exchange and size-exclusion chromatography, formulated with the adjuvant QS-21, and used to immunize BALB/c mice. Upon pulmonary challenge with either 035E or the heterologous isolate TTA24, significantly fewer bacteria were recovered from the lungs of immunized mice 6 h postchallenge than from control mice. The immune sera from mice or guinea pigs contained high titers of antibodies to the homologous isolate and heterologous isolates in a whole-bacterial-cell enzyme-linked immunosorbent assay. Sera against UspA, whether prepared in mice or guinea pigs, had complement-dependent bactericidal activity toward homologous and 11 heterologous M. catarrhalis isolates. These results indicate that the conserved epitopes of the UspA are highly immunogenic and elicit broadly reactive and biologically functional antibodies. UspA may offer protection against M. catarrhalis infections and is being further evaluated as a vaccine candidate.